Analysis of Mechanical Design Manufacture and Automation Characteristics, Advantages and Development Trends. (November 2020) - Wei, Li
Abstract: Mechanical manufacturing design is an important direction in the field of automation in China which promotes the development of China's productivity and economy. Based on this, this paper discusses the advantages and trends of automation in mechanical manufacturing so as to improve the efficiency of machinery manufacturing and promote economic development. Therefore, it is hoped that this paper can provide some references for related researchers.